Design and development of small scale wind turbine for low power application using Autocad - Norsuzilawati, Hussin (2021)
Awareness about the important of renewable energy such as solar, wind and geothermal as a primary alternative to non-renewable energy sources has been increase among the world society. Many country like United Kingdom, Spain, United State of America and Japan has started to develop a renewable technology especially wind energy in order to supply electricity to their citizen. In Malaysia the wind energy is not widely used for power generation as the average wind speed which is about 3-6 mis (East Coast region) make it not very efficient for large scale of power production. However, a small scale of wind turbine can be used to generate an electricity from a low wind speed. This small capacity of electricity that generated by the wind turbine can be useful to many situation. For example, during an emergency or disaster where there is a shortage in electrical supply, the small scale wind turbine can be used to charge up a telecommunication device such as phone to make an emergency call at the disaster area. Other than that, the small scale wind turbine can also be utilize at rural area where there is no electrical supply to power up a small device. On the surface of the Earth, wind consists of the bulk movement of air. The wind is also important for uses of transportation for seeds and small birds, with time things can travel thousands of miles in the wind. Wind is important to humans because wind energy is a source of renewable energy. It does not contaminate, it is inexhaustible and reduces the use of fossil fuels, which are the origin of greenhouse gasses that cause global warming. Wind energy does not generate waste or contaminate water which is extremely important factor given the scarcity of water. In this project, our group want to build a small scale wind turbine. Below are the specifications of this small scale wind turbine.